Composition and antibacterial activity of the essential oil of Artemisia nilagirica var. septentrionalis from India. Issue 1 (2nd January 2016) - Goswami, Prakash; Chauhan, Amit; Verma, Ram S.; Padalia, Rajendra C.; Verma, Sajendra K.; Darokar, Mahendra P.; Chanotiya, Chandan S.
Abstract: Essential oil composition of the aerial parts of Artemisia nilagirica (Clarke) Pamp. var. septentrionalis Pamp. was analyzed by GC-FID and GC-MS methods. Altogether forty-one constituents were identified, accounting for 95.9% of total composition. The essential oil was characterized by monoterpenoids (76.6%) represented by artemisia ketone (62.6%), artemisia alcohol (3.7%), perillene (3.1%), bornyl acetate (1.4%), along with sesquiterpenoids (16.1%) viz. β-caryophyllene (3.5%), α-muurolol (3.5%), δ-cadinene (2.1%) and germacrene D (1.8%). Essential oil was tested against nine pathogenic bacterial strains viz. Staphylococcus aureus (MTCC 96), Staphylococcus aureus (MTCC 2940), Streptococcus mutans, Staphylococcus epidermidis, Bacillus subtilis, Klebsiella pneumoniae, Escherichia coli, Pseudomonas aeruginosa, and Salmonella typhimurium. Based on zone of inhibition and MIC/MBC results, it is concluded that the essential oil of A. nilagirica var . septentrionalis exhibited good antibacterial activity against Staphylococcus aureus (MTCC-2940), Staphylococcus aureus (MTCC-96) and Bacillus subtilis, and moderate activity against Escherichia coli, Staphylococcus epidermidis, Salmonella typhimurium, and Streptococcus mutans.